Conjugate gradient algorithm and fractals - Mohamed Lamine Sahari; Ilhem Djellit (Discrete Dynamics in Nature and Society)
This work is an extension of the survey on Cayley's problem in case where the conjugate gradient method is used. We show that for certain values of parameters, this method produces beautiful fractal structures.